2006
DOI: 10.1021/jp061981q
|View full text |Cite
|
Sign up to set email alerts
|

Raman Microscopy for the Chemometric Analysis of Tumor Cells

Abstract: Raman spectroscopy is recognized as a tool for chemometric analysis of biological materials due to the high information content relating to specific physical and chemical qualities of the sample. Thirty cells belonging to two different prostatic cell lines, PNT1A (immortalized normal prostate cell line) and LNCaP (malignant cell line derived from prostate metastases), were mapped using Raman microscopy. A range of spectral preprocessing methods (partial least-squares discriminant analyses (PLSDAs), principal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 26 publications
3
84
1
Order By: Relevance
“…Normal Raman signals from cells and their infrared (FTIR) absorbance patterns have been previously used to differentiate between cancer and normal cells (6)(7)(8)(9). SERS has been used as an alternative immunohistochemistry (IHC) tool (10,11) for the detection of biomarkers in biological fluids or in vivo (12), and for cancer detection from blood (13).…”
mentioning
confidence: 99%
“…Normal Raman signals from cells and their infrared (FTIR) absorbance patterns have been previously used to differentiate between cancer and normal cells (6)(7)(8)(9). SERS has been used as an alternative immunohistochemistry (IHC) tool (10,11) for the detection of biomarkers in biological fluids or in vivo (12), and for cancer detection from blood (13).…”
mentioning
confidence: 99%
“…New Raman bands appeared in the region between 1150 and 1700 cm −1 , related to base structures and base-pairing, with higher intensities than the peaks in the spectra of the untreated cells. It has been shown that bands assigned to localised vibrations of these bases exhibit pronounced intensity increases during DNA melting [21]. The peaks in this region which showed hyperchromic behaviour are 1340, 1487 and 1578 cm −1 representing purine bases and 1378 cm −1 representative of pyrimidine bases [8], [21] and [22].…”
Section: Impact Of Increasing Concentrations Of Ethanolic Extract Of mentioning
confidence: 99%
“…It has been shown that bands assigned to localised vibrations of these bases exhibit pronounced intensity increases during DNA melting [21]. The peaks in this region which showed hyperchromic behaviour are 1340, 1487 and 1578 cm −1 representing purine bases and 1378 cm −1 representative of pyrimidine bases [8], [21] and [22]. A peak appeared at 1262 cm −1 , which is usually attributed to protonated cytosine, but the amount of plant extract used could not have lowered the pH to such an extent as to protonate cytosine [14].…”
Section: Impact Of Increasing Concentrations Of Ethanolic Extract Of mentioning
confidence: 99%
“…To enhance our ability to resolve SERS spectra more efficiently, we evaluated Principal Component Analysis (PCA), an approach often used to reduce the dimensionality of spectroscopic data (18)(19)(20), to resolve our four SERS tags. Spectra acquired from the Raman Spectral Flow Cytometer were smoothed, normalized and the first derivative calculated and subjected to PCA.…”
Section: Multivariate Statistical Approaches To Resolving Raman Spectmentioning
confidence: 99%